The Non-Objective World 1939-1955. - Rickey, George; Galerie Liatowitsch, Basel; Galleria Milano, Milano (London : Annely Juda Fine Art, 1972)
Adams, Robert ; Agam, Yaacov ; Albers, Josef ; Albrecht, Joachim ; Arp, Hans (Jean) ; Badiali, Carla ; Baertling, Olle ; Baljeu, Joost ; Bauer, Rudolf ; Baumeister, Willi ; Bayer, Herbert ; Beothy, Etienne ; Bergmann-Michel, Ella ; Biederman, Charles ; Bill, Max ; Bolotowsky, Ilya ; Bonfanti, Arturo ; Buchheister, Carl ; Cahn, Marcelle ; Calder, Alexander ; Carter, Clarence ; Charchoune, Serge ; Clark, Lygia ; Delaunay, Sonia ; Dewasne, Jean ; Deyrolle, Jean ; Diller, Burgoyne ; Domela, César ; Dorazio, Piero ; Elliott, Ronnie ; Fleischmann, Adolf Richard ; Flocon, Albert ; Fontana, Lucio ; Fontené, Robert ; Freundlich, Otto ; Gabo, Naum ; Gear, William ; Gilbert, Stephen ; Glarner, Fritz ; Gorin, Jean ; Graeser, Camille ; Heath, Adrian ; Hepworth, Barbara ; Herbin, Auguste ; Heurtaux, André ; Hill, Anthony ; Hinterreiter, Hans ; Huszar, Vilmos ; Itten, Johannes ; Kandinsky, Wassily ; Klee, Paul ; Kupka, Frantisek ; van der Leck, Bart ; Leppien, Jean ; Loewensberg, Verena ; Lohse, Richard ; Magnelli, Alberto ; Mari, Enzo ; Martin, Kenneth ; Martin, Mary ; Michel, Robert ; Moholy-Nagy, Laszlo ; Mondriaan, Piet ; Mortensen, Richard ; Morton, Alistair ; Munari, Bruno ; Nebel, Otto ; Nicholson, Ben ; Nigro, Mario ; Nouveau, Henri ; Pasmore, Victor ; Poliakoff, Serge ; Radice, Mario ; Reggiani, Mauro ; Reichel, Hans ; Rho, Manlio ; Rickey, George ; de Rivera, Jose ; Rothschild, Judith ; Schoffer, Nicolas ; Schwitters, Kurt ; Snelson, Kenneth ; Soldati, Atanasio ; Soto, Jesus Rafael ; Stazewski, Henryk ; Stephenson, Cecil ; Swinden, Albert ; Taeuber-Arp, Sophie ; Valensi, Henry ; Vasarely, Victor ; Veronesi, Luigi ; Vezelay, Paule ; Vordemberge-Gildewart, Friedrich ; Walkowitz, Abraham ; Wiegand, Charmion Von ; Winter, Fritz
biog. per kunstenaar
Duits & Engels & Italiaans
The Non-Objective World 1939-1955, Annely Juda Fine Art, London, 6 July - 8 September 1972 ; Die Gegenstandslose Welt 1939-1955, Galerie Liatowitsch, Basel, 20 September - 26 Oktober 1972 ; Il Mondo della Non-Oggettività 1939-1955, Galleria Milano, Milano, 14 Novembre - 30 Decembre 1972
boek